Exploring the Impact of Ohio Agricultural Organizations’ Social Media Use on Traditional Media Coverage of Agriculture - Leigha Haller; Annie R. Specht; Emily B. Buck (Journal of Applied Communications, 2019)
One of the nation’s most important industries, agriculture, has adopted social media to communicate with consumers and the public. At the same time, traditional news media remains important to the agriculture industry because many consumers still receive information about agriculture from sources such as newspapers and television. Little literature at the time of this study explored how social media is used specifically as a media relations tool. The purpose of this study is to examine how agricultural organizations in Ohio communicate via social media and how the messages could impact central Ohio traditional media outlets’ coverage of agricultural issues. The study is grounded in uses and gratifications theory, and previous social media studies. Data were collected from seven Ohio agricultural organizations’ Facebook pages and four central Ohio news outlets. Researchers found that Ohio agricultural commodity organizations use social media, but not necessarily to communicate with the news media. The industry received limited news coverage during the time studied, and we were unable to discern a relationship between social media and news media coverage beyond a commonality of stories. By communicating the results of this study with agricultural organizations and researchers, effective social media strategies can be developed to guide the future of social media as a media relations tool.
Keywords: Social media; media relations; news media